A new species of sucking louse (Phthiraptera: Anoplura) from Australia, and a key to the Australian species of Hoplopleura - Weaver, Haylee J.; Barton, Philip S. (Zootaxa, 2008)
A new species of sucking louse, Hoplopleura zyzomydis, is described and illustrated from the common Australian rock rat Zyzomys argurus (Thomas, 1889) (Rodentia: Muridae), collected in northwest Queensland, Australia. This is the first record of a sucking louse from the genus Zyzomys, and its morphology is contrasted with other Australian Hoplopleura species. Hoplopleura zyzomydis is unique in having a combination of short dorsal principal thoracic setae and setae absent from paratergal plates 4–6. A key to the Australian species of Hoplopleura is presented.